Advances in Control System Technology for Aerospace Applications - Feron, Eric (Lecture Notes in Control and Information Sciences,, 2016)
This book is devoted to Control System Technology applied to aerospace and covers the four disciplines Cognitive Engineering, Computer Science, Operations Research, and Servo-Mechanisms. This edited book follows a workshop held at the Georgia Institute of Technology in June 2012, where the today's most important aerospace challenges, including aerospace autonomy, safety-critical embedded software engineering, and modern air transportation were discussed over the course of two days of intense interactions among leading aerospace engineers and scientists. Its content provide a snapshot of today's aerospace control research and its future, including Autonomy in space applications, Control in space applications, Autonomy in aeronautical applications, Air transportation, and Safety-critical software engineering.